Implementation of an enhanced recovery protocol at a safety net hospital: a silver lining to COVID-19?. (1st October 2021) - Taylor, Adam J.; Kay, Robert D.; Tye, Erik Y.; Bryman, Jason A.; Longjohn, Donald; Najibi, Soheil; Runner, Robert P.
Abstract : Aims: This study aimed to evaluate whether an enhanced recovery protocol (ERP) for arthroplasty established during the COVID-19 pandemic at a safety net hospital can be associated with a decrease in hospital length of stay (LOS) and an increase in same-day discharges (SDDs) without increasing acute adverse events. Methods: A retrospective review of 124 consecutive primary arthroplasty procedures performed after resuming elective procedures on 11 May 2020 were compared to the previous 124 consecutive patients treated prior to 17 March 2020, at a single urban safety net hospital. Revision arthroplasty and patients with < 90-day follow-up were excluded. The primary outcome measures were hospital LOS and the number of SDDs. Secondary outcome measures included 90-day complications, 90-day readmissions, and 30day emergency department (ED) visits. Results: The mean LOS was significantly reduced from 2.02 days (SD 0.80) in the pre-COVID cohort to 1.03 days (SD 0.65) in the post-COVID cohort (p < 0.001). No patients in the pre-COVID group were discharged on the day of surgery compared to 60 patients (48.4%) in the post-COVID group (p < 0.001). There were no significant differences in 90-day complications (13.7% (n = 17) vs 9.7% (n = 12); p = 0.429), 30-day ED visits (1.6% (n = 2) vs 3.2% (n = 4); p = 0.683), or 90-day readmissions (2.4% (n = 3) vs 1.6% (n = 2); p = 1.000) between the pre-COVID and post-COVID groups, respectively. Conclusion: Through use of an ERP, arthroplasty procedures were successfully resumed at a safety net hospital with a shorter LOS and increased SDDs without a difference in acute adverse events. The resulting increase in healthcare value therefore may be considered a 'silver lining' to the moratorium on elective arthroplasty during the COVID-19 pandemic. These improved efficiencies are expected to continue in post-pandemic era. Cite this article: Bone Jt Open 2021;2(10):871–878.